An experimental study on post-punching behavior of flat slabs. (October 2020) - Sarvari, Saeed; Esfahani, M. Reza
Highlights: The increase of the concrete cover enhances post-punching strength. Decrease of the diameter of tensile reinforcement, the post-punching strength increases. Truss reinforcement increases punching and post-punching strengths. Bent-up integrity reinforcement increases punching and post-punching strength. Additional bent-up reinforcement was not effective on the post-punching strength. Abstract: If unpredictable loads are applied to flat slab-column connections, punching shear failure occurs with almost no warning signs. To prevent progressive collapse of flat slab-column connections, it is necessary to provide a secondary load carrying mechanism after punching shear failure. In this research, some suggestions for establishing an alternative mechanism in flat slab connections after punching failure are proposed. For this purpose, an experimental program was conducted to investigate the post-punching behavior of 17 slabs with various reinforcement layouts and concrete covers. The effects of integrity, compressive, shear, truss, and bent-up reinforcements, diameter of tensile reinforcement, and concrete cover of tensile reinforcement on the post-punching behavior of slab-column connections were studied. The results of the experiments indicate that the integrity reinforcement significantly improves the post-punching strength. The increase of the concrete cover of the tensile reinforcement and decrease of the diameter of the tensile reinforcement result in an increase of the post-punching strength. Bent-up integrity reinforcement increases the punching and post-punching strengths, simultaneously. Truss reinforcement significantly improves the punching and post-punching behavior.